Legal Construction of International Business Contracts as an Instrument for Strengthening Banana Cracker Exports and Ogan Banana Supply Chain Management in Lumajang Regency - Ratnaningsih; Sudjatmiko; Hastuti, Sri; Maulidandi, Muhammad Akmal Naufaldi (LITIGASI, 2025)
Today's entrepreneurs prioritize international trade as an important goal in business development, which leads to the formation of international business contracts, but not all entrepreneurs understand the various regulations related to international business contracts, dispute resolution in the event of a dispute, and legal certainty in the event of force majeure. In addition, this study also wants to analyze the provisions for the use of Indonesian in agreements based on Law of the Republic of Indonesia Number 24 of 2009 concerning the Flag, Language, and National Emblem, as well as the National Anthem, with an analytical knife using the principle of freedom of contact. This research related to international business contracts was inspired by the desires of home industry entrepreneurs in Nogosari Village, Rowokangkung District, Lumajang Regency, who produce "banana crackers" and want to spread their wings into the world of international trade. In addition to understanding the various rules of international business contracts, banana crackers entrepreneurs also face the problem of difficulty in obtaining organic banana raw materials. Fruits have a high water content so they are easily damaged and have a short shelf life. Bananas are a type of fruit that is easily damaged, so there must be a solution, namely producing banana products, one of which is banana crackers and analyzing the management of the Supply Chain....